An Updated Review of Randomized Clinical Trials Testing the Improvement of Cognitive Function of Ginkgo biloba Extract in Healthy People and Alzheimer’s Patients - Liu, Haolong; Ye, Min; Guo, Hongzhu (Frontiers in Pharmacology, 2020)
Alzheimer’s disease (AD) is a common neurodegenerative disease, mainly manifested by cognitive dysfunction. It seriously reduces the quality of life, and there is no ideal treatment strategy in clinical practice. Clinical studies on the treatment of AD with Ginkgo biloba L. leaf extract (EGb) have been reported since 1980s, and many clinical studies have been carried out during the following 30 years. However, the benefits of EGb on the treatment of AD are still controversial. In this review, we collected the clinical trial reports of EGb on cognitive function from Pubmed, Elsevier, Europe PMC and other data base since the 1980s. Through analysis and comparison, we consider that EGb may be able to improve the cognitive function in patients suffered from mild dementia during long-term administration (more than 24 weeks) and appropriate dosage (240 mg per day). The main evidences and existing problems of the negative and positive experimental results were summarized.